Cholesterol's Interfacial Interactions with Sphingomyelins and Phosphatidylcholines: Hydrocarbon Chain Structure Determines the Magnitude of Condensation() - Smaby, Janice M. (1994)
Cholesterol's interfacial interaction with different sphingomyelins and phosphatidylcholines has been investigated using a Langmuir film balance. The average molecular area of cholesterol/sphingomyelin (SM) or cholesterol/phosphatidylcholine (PC) mixed monolayers was determined as a function of film composition from the force–area isotherms measured at 24 °C. In contrast to previous results, little difference was observed in equimolar cholesterol's “condensing effect” of SMs compared to PCs when their phase state was similar and when their hydrocarbon structural differences were minimized. For PCs, this meant that one acyl chain had to be long and capable of assuming an extended conformation and thus configurationally similar to the long-chain base of SM. This condition facilitated strong van der Waals attractive interactions with cholesterol's planar steroid ring and was satisfied when the sn-1 acyl chain of PC was either myristate or palmitate. Under these conditions, the structural requirements of the sn-2 chain of PC were mitigated. For instance, at equimolar cholesterol, almost no difference was observed in the apparent molecular area condensations of 1-palmitoyl-2-oleoyl-PC and 1-palmitoyl-2-arachidonoyl-PC at surface pressures between 10 and 40 mN/m. In contrast, the apparent molecular area condensations of dioleoyl-PC and diarachidonoyl-PC were substantially reduced under identical experimental conditions. The results are discussed in terms of the relative importance of phospholipid/sphingolipid hydrocarbon and headgroup structure in determining the extent of interaction with cholesterol. Conclusions were based on investigation of egg SM, bovine brain SM, N-oleoyl-SM, dipalmitoyl-PC, dimyristoyl-PC, 1-myristoyl-2-palmitoyl-PC, 1-palmitoyl-2-oleoyl-PC, 1-palmitoyl-2-arachidonoyl-PC, dioleoyl-PC, dinervonoyl-PC, diarachidonoyl-PC, and diphytanoyl-PC as well as comparison with cholesterol's condensation of various galactosylceramide molecular species.